Educational impact of Metaverse learning environment for engineering mechanics dynamics - Sidhu M.S.; Mousakhani S.; Lee C.K.; Sidhu K.K. (John Wiley and Sons Inc, 2025)
Mechanics dynamics course is challenging for mechanical engineering students. Strong abilities in abstract thinking, reasoning, and problem-solving are prerequisites for this course. Technology advancements in Industrial Revolution 4.0 have brought about significant changes in engineering education, and traditional teaching methods may no longer be sufficient to prepare students for the requirements of this industrial revolution. Relating to all Internet technologies, the Metaverse is an emerging environment that allows immersive interactive experiences to enhance comprehension. Combining Metaverse with constructivist learning, students can engage in engineering tasks and receive real-time feedback for deeper understanding. Education 5.0 emphasizes the use of new applications and technology to provide more humanized education, with an emphasis on students' social and emotional growth and solutions that improve life in society. However, since the Metaverse learning environment is still in its infancy, more empirical research is required regarding the application of the Metaverse environment using a constructivist approach to facilitate teaching and learning in engineering, particularly in the setting of mechanics dynamics. This research proposal aims to investigate and design a conceptual framework for the Metaverse environment as an additional learning aid in mechanical engineering education. The research findings could enhance the quality of mechanical engineering education, which is in line with the current Malaysia education blueprint that is, the incorporation of new educational technology aids and interventions. Additionally, the findings could provide new insights into the design of engineering curricula teaching practices and the Malaysian Science, Technology, Innovation, and Economy policy of providing new educational platforms that is, to nurture a creative society and a skilled workforce. ? 2024 Wiley Periodicals LLC.